2019
DOI: 10.1017/s0029665119000016
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional modulation of the epigenome and its implication for future health

Abstract: Non-communicable diseases (NCD) such as type-2 diabetes and CVD are now highly prevalent in both developed and developing countries. Evidence from both human and animal studies shows that early-life nutrition is an important determinant of NCD risk in later life. The mechanism by which the early-life environment influences future disease risk has been suggested to include the altered epigenetic regulation of gene expression. Epigenetic processes regulate the accessibility of genes to the cellular proteins that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 84 publications
(93 reference statements)
0
10
0
1
Order By: Relevance
“…Folic acid and Vitamin B12 therapy inhibit adipogenic development in 3T3-L1 cells via modulating Wingless and Int (Wnt) 10b ( Cordero, Gomez-Uriz, Campion, Milagro & Martinez, 2013 ). Burton et al., 2019 suggested the influence of methyl donors on adipogenesis through epigenetic alterations in processing genes.…”
Section: Epigenetic Control On Livestock Productionmentioning
confidence: 99%
“…Folic acid and Vitamin B12 therapy inhibit adipogenic development in 3T3-L1 cells via modulating Wingless and Int (Wnt) 10b ( Cordero, Gomez-Uriz, Campion, Milagro & Martinez, 2013 ). Burton et al., 2019 suggested the influence of methyl donors on adipogenesis through epigenetic alterations in processing genes.…”
Section: Epigenetic Control On Livestock Productionmentioning
confidence: 99%
“…Animal studies have also shown that changes in maternal intake during pregnancy that affect the availability of methyl donors can alter the epigenetic pattern of certain regions of the genome (metastable epi-alleles) in the early embryo that are stable in different tissues, causing permanent phenotypic variation in offspring [163]. In humans, although studies are still scarce, there is increasing evidence showing that perinatal nutrition may trigger persistent changes in DNA methylation [164]. For example, it has been shown that variations in methyl donor intake (associated with seasonal differences in diet: the rainy (‘hungry’) season and the dry (‘harvest’) season) in women of a rural population of Gambia during conception predict the methylation patterns of metastable epialleles in offspring [165,166].…”
Section: Nutrigenomic Approach In the Identification Of Biomarkersmentioning
confidence: 99%
“…CpG methylation is an epigenetic marker that is strongly affected by environmental factors such as diet, early life stress, or the life-styles led by our parents [ 71 ]. Environmentally altered CpG methylation, in turn, can modulate susceptibility to diseases such as depression, addiction and anxiety in subsequent generations [ 72 , 73 ].…”
Section: Nature Versus Nurture: Epigenetics and The Functional Nonmentioning
confidence: 99%